2020
DOI: 10.3390/ijerph17238975
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Mental Health in Mothers and Fathers Caring for Children and Adolescents with Rare Diseases Requiring Long-Term Mechanical Ventilation

Abstract: (1) Parents caring for children and adolescents with rare diseases fear the long-term progression of the child’s disease and the loss of their parental role. The aim of this study was to examine the quality of life, mental health and associated protective factors of mothers and fathers caring for children with rare diseases requiring mechanical long-term ventilation. (2) In a cross-sectional design, data on quality of life, mental health, coping mechanisms, social support and family functioning from n = 75 aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 35 publications
(54 reference statements)
4
26
0
2
Order By: Relevance
“…This re ects existing grey literature [3,5,30] and is consistent with ndings from condition-speci c studies which used diagnostic tools to measure anxiety and/or depression in rare disease patients and/or carers [20][21][22] and impact on quality of life. [17][18][19] Consistent with condition-speci c research [33][34][35][36], our ndings show that the negative impact on mental health can be chronic, and can occur or recur at different times such as during the 'diagnostic odyssey'; when a diagnosis is given; and while coming to terms with the condition. This highlights the periods when additional emotional support may be particularly important.…”
Section: Discussionsupporting
confidence: 82%
“…This re ects existing grey literature [3,5,30] and is consistent with ndings from condition-speci c studies which used diagnostic tools to measure anxiety and/or depression in rare disease patients and/or carers [20][21][22] and impact on quality of life. [17][18][19] Consistent with condition-speci c research [33][34][35][36], our ndings show that the negative impact on mental health can be chronic, and can occur or recur at different times such as during the 'diagnostic odyssey'; when a diagnosis is given; and while coming to terms with the condition. This highlights the periods when additional emotional support may be particularly important.…”
Section: Discussionsupporting
confidence: 82%
“…Correspondingly, previous studies suggest that parents of children with rare congenital surgical diseases score significantly lower on QoL [ 18 21 ] and mental health assessments [ 22 , 23 ]. Moreover, studies involving children with rare congenital surgical diseases have shown a significant reduction in parent-reported health-related quality of life (HRQoL) compared to healthy controls [ 24 28 ].…”
Section: Introductionmentioning
confidence: 81%
“…Caregivers have an extremely delicate role, which is indeed accompanied by increasing social and public concern. Being a caregiver acquires a relevant importance in the context of several chronic medical conditions because of the different and various needs of patients [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%